1992
DOI: 10.1073/pnas.89.23.11151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional expression of a brain-specific somatostatin receptor.

Abstract: The PCR and conventional library screening were used to clone the brain-specific somatostatin receptor rSSTR-4 from a rat genomic library. The deduced amino add sequence encodes a protein of 384 amino acids and displays structural and sequence homologies with members of the G protein-receptor superfamily. The , a cyclic tetradecapeptide, was originally isolated from ovine hypothalamus and found to have potent inhibitory effects on growth hormone and thyroidstimulating hormone secretion from the anterior pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(141 citation statements)
references
References 34 publications
1
138
0
2
Order By: Relevance
“…1A). [8][9][10][11] The genes for these subtypes are located on different chromosomes, suggesting different functions in different organs (Table 1). Indeed, distinct but often overlapping patterns in the expression of these subtypes have been demonstrated.…”
Section: S Omatostatin R Eceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). [8][9][10][11] The genes for these subtypes are located on different chromosomes, suggesting different functions in different organs (Table 1). Indeed, distinct but often overlapping patterns in the expression of these subtypes have been demonstrated.…”
Section: S Omatostatin R Eceptorsmentioning
confidence: 99%
“…There have been no reports of the loss of the suppressive effect of octreotide on growth hormone secretion in patients with acromegaly, even after more than 10 years of uninterrupted therapy. 38,43 The high cost of treatment with octreotide *Data on the five subtypes were obtained from the following reports: subtypes 1 and 2, Yamada et al 8 ; subtype 3, Yamada et al 9 ; subtype 4, Bruno et al 10 ; and subtype 5, O'Carroll et al 11 †IC 50 denotes the concentration required for 50 percent inhibition of the binding of 125 I-labeled somatostatin to the cloned subtype, as expressed in Chinese hamster-ovary or transformed African green-monkey COS kidney cells. Data were obtained from Patel and Srikant.…”
Section: Acromegalymentioning
confidence: 99%
“…Recently five somatostatin receptors have been cloned. They belong to the family of G protein-coupled receptors and can couple to diverse signal transduction pathways (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…activity was determined by measuring the rate of pH i recovery (dpH i /dt) from an NH 4 Cl-induced acid load in a nominally HCO 3 --free Hepes buffer (28). Cells plated on glass coverslips were maintained in the absence of serum for 16 -20 h before pH i determinations, transferred to a Hepes buffer, and loaded with the acetoxymethyl ester of the pH-sensitive fluorescent dye, 2,7-biscarboxyethyl-5-(6)-carboxyfluorescein (BECEF-AM, 1 M; Molecular Probes, Inc.) for 10 min at 37°C.…”
Section: Nhe1 Activity and Ph I -Nhe1mentioning
confidence: 99%
“…Receptor expression was determined by radioligand binding using [ We found that SSTR3 and -4, but not SSTR5, mediate SST inhibition of NHE1 activity. NHE1 activity was determined in a nominally HCO 3 Ϫ -free Hepes buffer and expressed as the rate of recovery of intracellular pH (pH i ) from an NH 4 Cl-induced acid load. SST (100 nM) had no effect on quiescent NHE1 activity in any of the SSTR-expressing cell lines (n ϭ 3; data not shown), in accordance with its inability to inhibit quiescent cAMP accumulation.…”
Section: Subtype-specific Coupling Of Sstr To the Inhibition Of Nhe1-mentioning
confidence: 99%